Improving Level of Algebraic Reasoning for Junior High School Students using Metacognitive Training (Jurusan Matematika FMIPA UNNES, 2020)
Mathematics as one of the sciences that discusses abstract concepts, certainly requires a good reasoning process in understanding it. One of reasoning in mathematics is algebraic reasoning, which used as a foundation for algebraic thinking. As one of the curriculum competences, the algebraic reasoning from Junior High School students is still in the low level. This article discusses how the initial conditions of algebraic reasoning level from Junior High School students, and how to improve it. One of ways that can be done is using metacognitive training. Metacognitive training gives freedom to students to solve the problems by themselves with some integration guidance. It is hoped that students will be able to guide themselves through the process of algebraic reasoning level improvement. There are some important things that should be considered to get the optimum result in improvement process. And also, the main discussion is how the metacognitive training can improve the algebraic reasoning level of Junior High School students.